2019
DOI: 10.20945/2359-3997000000149
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotypes of obese, overweight, and normal weight individuals and risk of chronic kidney disease: a systematic review and meta-analysis

Abstract: Objective: Chronic kidney disease (CKD) risk is inconsistent in the normal-weight, overweight, and obese individuals due to the heterogeneity of metabolic status. This meta-analysis aimed to examine the combined effects of body mass index (BMI) and metabolic status on CKD risk. Materials and methods: The MEDLINE, EMBASE, and Web of Knowledge databases were systematically searched up to March 2019 to identify all eligible studies investigating the CKD risk (defined as GFR < 60 mL/min per 1.73 m 2 and/or microal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 63 publications
(99 reference statements)
3
30
0
2
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24][25][26] In view of this, two systematic review and metanalyses have been performed, with 166,718 (from 4 studies) and 181,505 (from 11 studies) participants respectively, both showing higher risk of incident CKD in MHO compared with MHNW individuals. 19,41 However, the number of studies included in these two metanalyses were small and there were variable degrees of bias. There was also significant heterogeneity in sample size, length of follow-up, genetic background, the GFR estimation equation used, potential confounders controlled for, and the use of metabolically defined body size phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26] In view of this, two systematic review and metanalyses have been performed, with 166,718 (from 4 studies) and 181,505 (from 11 studies) participants respectively, both showing higher risk of incident CKD in MHO compared with MHNW individuals. 19,41 However, the number of studies included in these two metanalyses were small and there were variable degrees of bias. There was also significant heterogeneity in sample size, length of follow-up, genetic background, the GFR estimation equation used, potential confounders controlled for, and the use of metabolically defined body size phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings persisted across multiple definitions of metabolic health ranging from the strict definition to the standard definition of MetS, demonstrating that one metabolic risk factor may be similarly indicative of renal dysfunction as two or three risk factors but that CKD status was more highly dependent upon ACR than eGFR. The MUN phenotype, while not typically perceived as high risk [ 10 ], has been correlated with adverse health outcomes, such as poor renal function [ 23 ], type 2 diabetes, cardiovascular events, and mortality [ 35 ]. In our study as well as previously reported findings [ 17 , 23 ], the MUN phenotype was correlated with older age.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic phenotypes, which take into account metabolic risk factors and obesity, have been utilized to assess the risk of various outcomes, such as cardiovascular disease (CVD), mortality, and CKD. A recent meta-analysis by Alizadeh et al [10] analyzed nine prospective cohort studies that compared CKD risk among metabolic phenotypes and Life 2021, 11, 888. https://doi.org/10.3390/life11090888 https://www.mdpi.com/journal/life found that the metabolically healthy obese (MHO) and the metabolically unhealthy normal weight (MUN), termed the "intriguing" phenotypes, shared a similarly elevated risk of developing CKD, with pooled relative risks (RR) of 1.55 and 1.58, respectively. This meta-analysis included studies with primarily Asian populations, limiting generalizability, and the definitions of the metabolic phenotypes varied, hindering the comparability between studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a strong association of MetS with the development and severity of renal dysfunction and chronic kidney disease (CKD) [108][109][110]. MetS patients have a several-fold higher risk of developing CKD and it is often shown that renal dysfunction manifests earlier than diabetes in MetS patients [111].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%